Possible Roles of Membrane Trafficking Components for Lipid Droplet Dynamics in Higher Plants and Green Algae - Huang, Shuxian; Jiang, Liwen; Zhuang, Xiaohong (Frontiers in Plant Science, 2019)
Lipid droplets are ubiquitous dynamic organelles that contain neutral lipids surrounded by a phospholipid monolayer. They can store and supply lipids for energy metabolism and membrane synthesis. In addition, protein transport and lipid exchange often occur between LDs and various organelles to control lipid homeostasis in response to multiple stress responses and cellular signaling. In recent years, multiple membrane trafficking proteins have been identified through LD proteomics and genetic analyses. These membrane trafficking machineries are emerging as critical regulators to function in different LD-organelle interactions e.g. for LD dynamics, biogenesis and turnover. In this review, we will summarize recent advances in regard to LD-related membrane trafficking proteins and discuss future investigations in higher plants and green algae.